Mapping the Global Research Landscape on the Nurse Resilience Management: A Bibliometric Analysis - Us Yana; Gerulaitienė Neringa (Economics and Business)
Global critical events such as the COVID-19 pandemic significantly influence the healthcare system, particularly healthcare workers. In this view, more studies emphasized the necessity to increase healthcare resilience. However, the systematization of the literary sources showed no bibliometric studies devoted to a comprehensive investigation of nurse resilience management. The main aim of this study is to analyse the status of the global research landscape on nurse resilience management and detect the forthcoming trends in this research field. The research questions are as follows: 1) What is the current status of research on nurse resilience management? 2) What are the future research directions for developing nurse resilience management? The research object is the scientific documents published in high-quality scientific journals indexed in the Web of Science database. The total sample of publications is 245 documents. The study period covers 2005–2022 (up to 7 September 2022). The study involved bibliometric and knowledge visualization methods to achieve the research goal. The research was conducted in the following logical sequence: 1) collecting and pre-processing data; 2) analysing and visualizing data (general statistics, collaboration networks, and research trends); 3) interpreting results and discussing future research directions. The findings of bibliometric analysis allowed analysing the dynamic of publication activity, detecting the most influential articles, sources, and researchers, as well as setting up a typology of the themes of the analysed scope of literature.